Թիգլաթպալասար I-ի հյուսիսային ռազմարշավները, նպատակներն ու արդյունքները - Ցականյան, Ռուսլան Ա. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В период правления Тиглатпаласара (Tukultī-apil-Ešarra) I (1114-1076 гг. до н. э.), одного из последних могущественных царей Среднеассирийского государства (ок. последней четверти XV в. до н. э. — первой половины X в. до н. э.), безопасность его северных и северо-западных границ имела для государства большое стратегическое значение. В результате анализа клинописных источников предпринята попытка реконструировать стратегические и экономические цели его походов на Армянское нагорье и в восточную часть Малой Азии, а также раскрыть их историческое значение. Северные походы Тиглатпаласара I представляли собой продуманную завоевательную стратегию, направленную на обеспечение торговых путей, доступа к ценным ресурсам и установление господства Ассирии над малыми и средними государствами региона. During the reign of Tiglath-Pileser (Tukultī-apil-Ešarra) I (1114-1076 BC), one of the last powerful kings of the Middle Assyrian Empire (c. the last quarter of the 15th century BC – the first half of the 10th century BC), the security of its northern and northwestern borders was of great strategic importance to the state. An analysis of cuneiform sources has made it possible to reconstruct the strategic and economic goals of his campaigns in the Armenian Highlands and in eastern Asia Minor, as well as to reveal their historical significance. The northern campaigns of Tiglath-Pileser I were a well-thought-out strategy of conquest aimed at securing trade routes, access to valuable resources, and establishing Assyria’s dominance over the small and medium-sized states of the region.
Keywords: Պատմություն